(3QSGdI aj GdGSWQdGHs
(3ChdgG (B:s
(3GdMeO ddg MeOkG Hdjb HLdGdI hHYO agPg QSGdI eNJUQI GPcQ ajgG GSeGA GdQShe GdeQSheI Ydi GdGdI GdeSeGg HGdGTWQGdGH s
(3BNQgG (B:s
(3hEf cGf GdGQJaGY TQbjkG hGdG agh GdHGbj ddZQhH eY RjGOI fUa GdJYOjd aj GdTeGd s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs